INTEGRATING BIOMEDICAL ENGINEERING AND EMERGENCY MEDICAL SERVICES: A CRITICAL REVIEW OF THEIR VITAL ROLES IN ENHANCING PUBLIC HEALTH OUTCOMES - Salem Ali Mohammed Alsaab, Ali Suliman Ali Alsaab, Salem aliHadialduways, Saleh hussainhassanalabbas, Mohammed Ali Saleh ALAbdullah, Hatem Nasser Ali Al sarour (Chelonian Research Foundation, 2023)
This critical review explores the synergistic integration of biomedical engineering (BME) and emergency medical services (EMS) in enhancing public health outcomes. By intertwining BME's technological innovations with the operational framework of EMS, this interdisciplinary approach promises to elevate the quality of emergency care, patient safety, and the overall efficiency of healthcare systems. Through an examination of current practices, recent advancements in BME such as wearable technologies, telemedicine, and advanced diagnostics are highlighted for their potential to revolutionize emergency medical responses. This article delves into the challenges and opportunities presented by the integration, including interoperability, privacy concerns, and the need for specialized training. It also investigates future directions, emphasizing the importance of collaboration between engineers, healthcare professionals, and policymakers. By critically reviewing the current state and projecting future innovations, this article underscores the transformative impact of integrating BME with EMS on public health. Keywords: Biomedical Engineering, Emergency Medical Services, Public Health, Technological Innovations, Wearable Technologies, Telemedicine, Advanced Diagnostics, Interoperability, Privacy, Training, Future Directions, Interdisciplinary Collaboration.